La otra herencia de Magón. Homenaje de un lector a Manuel González Zeledón (Magón, 1864-1936) en el 70 aniversario de su muerte - Vargas, José A. (2013)
Manuel González Zeledón (Magón, 1864-1936) lawyer and writer, is the author of Cuentos, of which the first complete edition was published by the Universidad de Costa Rica in 1947. In this article an analysis is made of the references on coins and paper money made by Magón in 26 of his 44 cuentos. A total of 173 references of numismatic interest provide the reader with a view of the cost of living in the city of San José from about 1871 to 1910. The most often cited coins are the reales (36 times), followed by the pesos (29), the 5 and 10 cents coins (14), and the gold colones (12). Magón was probably aware of the usefulness of this information for future generations. However, this legacy dispersed in his Cuentos, has not received attention until now.